1951
DOI: 10.1214/aoms/1177729550
|View full text |Cite
|
Sign up to set email alerts
|

One-Sided Confidence Contours for Probability Distribution Functions

Abstract: Sensitivity contours are used to examine the effect of outliers on a test of normality based on sampleentropy. The contours are comparedwith those of the Shapiro-Wilk W-test and it is shown that the entropy test is considerably less sensitive to outliers than the W-test. This is illustrated using the results of a confounded 2& factorial experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(71 citation statements)
references
References 1 publication
0
71
0
Order By: Relevance
“…The Birnbaum-Tingey onesided contour analysis was used for the one-sided Kolmogorov-Smirnov test. It takes variance into account and can indicate if the CDF of one set of samples is larger than the CDF of the other set [9], [37]. It also returns a p-value for the assertion.…”
Section: Statistical Analysis Of Resultsmentioning
confidence: 99%
“…The Birnbaum-Tingey onesided contour analysis was used for the one-sided Kolmogorov-Smirnov test. It takes variance into account and can indicate if the CDF of one set of samples is larger than the CDF of the other set [9], [37]. It also returns a p-value for the assertion.…”
Section: Statistical Analysis Of Resultsmentioning
confidence: 99%
“…We can also perform formal goodness of fit test in order to verify which distribution fits to the data. We apply the Kolmogorov-Smirnov test (KS test) [18] and Anderson-Darling test (AD test) [19] for the goodness of fit purpose. Table 2 lists the MLE estimates of the parameters β and θ and values of the test statistics which are KS test and AD test.…”
Section: Discussionmentioning
confidence: 99%
“…We used a t-test in order to ensure that the two density functions are different and the resulted p-value was < 1%. Because of the fact that the two pdfs are not Gaussian, we have also applied the Kolmogorov-Smirnov test or KS-test [3] that does not require normal pdfs. The Kolmogorov-Smirnov test indicated that, indeed, the normal and abnormal samples come from different pdfs (p-value = 2.09e-07).…”
Section: Offline Experimentsmentioning
confidence: 99%